The acquisition of noun prefixes and suffixes during coloring activities among Malay children - Baharon, Burhan Murshidi; Sha’r, Sharil Nizam; Kamaruddin, Rohaidah (Human Resource Management Academic Research Society, 2023)
This study of Psycholinguistics emphasizes the development of noun prefixes and suffixes among Malay children. The objective of the study was to identify the development of noun prefixes and suffixes among Malay children aged eight, nine, and 10 years. This study applies the Mentalist Theory and was conducted through six respondents consisting of both males and females in each age group. The children consisted of native speakers of Malay, and this study was conducted within the respondent's home. The data of this study was obtained through coloring activities where the respondents would story-tell while being engaged in the the activity. The findings of this study discusses the role of language input on the development of noun prefixes and suffixes and further proves that the acquisition involves cognitive, social, and linguistic processes.